Treatment planning principles for orthodontic-surgical correction of dento-facial anomalies - Vig Katherine W.L (Sciendo, 1980)
The development of a combined orthodontic and surgical approach to the treatment of dento-facial anomalies has resulted in the close collaboration of the oral surgeon and orthodontist in the diagnosis, treatment planning, and management of these cases. Although many dento-facial anomalies are just extremes of normal variations, the methods used in orthodontics for evaluating facial balance and aesthetics can be applied to developmental and congenital anomalies in which the facial complex is deformed, deficient, or out of proportion. Methods of clinical and radiographic assessment are described and the sequencing and timing of treatment in the growing child discussed. Special reference is made to the cleft palate patient in which the same methods of evaluation are applied.